Experimental study on the freezing process of a supercooled horizontal water bridge between cold fins. (January 2023) - Wu, Xin; Gong, Jianying; Jin, Long; Hou, Jianqiang; Liu, Gaoyi
Abstract: In this study, a series of experiments were conducted to comprehensively investigate the freezing process of a static supercooled horizontal water bridge between cold fins. How cold surface temperatures, water bridge volumes, and air relative humidities with a wide range of variation effects on water bridge freezing were further explored. The dynamic evolutions of internal temperature, ice-water interface, and freezing time were revealed. Some particular deformation phenomena, such as ice rings and protruding droplets, were observed during the freezing process of the water bridge. The results indicate stable nucleation temperatures in the recalescence stage. It was found that whether nucleation and crystal growth occur depends on the nuclear energy barrier, and whether the nucleation temperature changes when nucleation occurs is determined by the stable nucleation temperatures. When the cold surface temperature is constant, the nucleation temperature decreases with the increase of water bridge volume and air relative humidity, respectively. Compared with water bridge volume, cold surface temperature and air relative humidity have a more significant effect on water bridge freezing. Furthermore, the lower the cold surface temperature, water bridge volume, and air relative humidity, respectively, the shorter the freezing time and the faster the movement velocity of the ice-water interface. In addition, a semi-empirical correlation is proposed to predict the movement distance of the ice-water interface, which can accurately predict 95% of the considered experimental data with a deviation of ±25%.